Legal Digest Vol. 2 2009 / Law Department UiTM Terengganu - UiTM Terengganu, Law Department (Universiti Teknologi MARA, Terengganu, 2009)
Legal Digest brings you various interesting articles that are very much related to our daily lives, written by Law Department UiTM Terengganu members.